2019
DOI: 10.7146/torture.v29i1.106613
|View full text |Cite
|
Sign up to set email alerts
|

The role of a trauma-sensitive football group in the recovery of survivors of torture

Abstract: Introduction: Whilst there is some preliminary evidence for the benefits of sports-related interventions for survivors of torture, how sport and exercise can contribute to the rehabilitation of torture survivors needs to be better understood. Specifically, this paper aims to: 1) explore the ways in which a football group contributed to the wellbeing of participants and; 2) suggest characteristics of the football group which could potentially contribute to its effectiveness. Methods: An exploratory mixed method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Specific cultural beliefs about physical activity, which often arise from different ethnic identities and exposures, play a strong role in people's decision to adopt a physical activity program [32][33][34][35]. For survivors of torture, trauma-sensitive soccer proved to be a critical factor for regaining access to one's body, building social relationships, and learning to cope with stressful events [36]. Moreover, a study involving children and adolescents found that after disasters, sports and exercise are able to promote emotional and social stabilization and improve resilience [37].…”
Section: Introductionmentioning
confidence: 99%
“…Specific cultural beliefs about physical activity, which often arise from different ethnic identities and exposures, play a strong role in people's decision to adopt a physical activity program [32][33][34][35]. For survivors of torture, trauma-sensitive soccer proved to be a critical factor for regaining access to one's body, building social relationships, and learning to cope with stressful events [36]. Moreover, a study involving children and adolescents found that after disasters, sports and exercise are able to promote emotional and social stabilization and improve resilience [37].…”
Section: Introductionmentioning
confidence: 99%